Profil Kemampuan Literasi Sains Peserta Didik di SMA Negeri Kabupaten Pinrang - Muhiddin Palennari; Andi Nur Safitri; Arifah Novia Arifin (Lembaga Penelitian Mahasiswa Penalaran UNM, 2022)
The aim of the study was to determine the profile of the scientific literacy ability of state high school students in Pinrang Regency. This study is a descriptive study with a survey method conducted on students of class X MIA SMAN in Pinrang Regency in 2020 on the subject of Biodiversity. The population in this study were 584 class X MIA students spread across SMAN 1 Pinrang, SMAN 4 Pinrang, SMAN 5 Pinrang and SMAN 9 Pinrang.The sample used in this study amounted to 272 students who were scattered from various high school study groups in selected by ramdom sampling. Based on the results of data analysis, it is known that the highest students' science literacy skills were in the medium category at 34.9%. Furthermore, 32.7% were in a low category, 24.3% were in the high category, 6.3% were in the very high category, and the remaining 1.8% were in the very low category. Although the science literacy skills of SMAN students in Pinrang Regency are in the moderate category. From the results of this study, it is suggested for biology teachers to be able to maximize the application of learning strategies that can train students' scientific literacy skills.